A unique binding mode of Nek2A to the APC/C allows its ubiquitination during prometaphase. (19th April 2020) - Alfieri, Claudio; Tischer, Thomas; Barford, David
Abstract: The anaphase‐promoting complex (APC/C) is the key E3 ubiquitin ligase which directs mitotic progression and exit by catalysing the sequential ubiquitination of specific substrates. The activity of the APC/C in mitosis is restrained by the spindle assembly checkpoint (SAC), which coordinates chromosome segregation with the assembly of the mitotic spindle. The SAC effector is the mitotic checkpoint complex (MCC), which binds and inhibits the APC/C. It is incompletely understood how the APC/C switches substrate specificity in a cell cycle‐specific manner. For instance, it is unclear how in prometaphase, when APC/C activity towards cyclin B and securin is repressed by the MCC, the kinase Nek2A is ubiquitinated. Here, we combine biochemical and structural analysis with functional studies in cells to show that Nek2A is a conformational‐specific binder of the APC/C–MCC complex (APC/C MCC ) and that, in contrast to cyclin A, Nek2A can be ubiquitinated efficiently by the APC/C in conjunction with both the E2 enzymes UbcH10 and UbcH5. We propose that these special features of Nek2A allow its prometaphase‐specific ubiquitination. Synopsis: The APC/C regulates mitosis by catalysing the sequential ubiquitination of specific substrates. This study shows how the APC/C ubiquitinates the Nek2A kinase in prometaphase when the APC/C is inhibited by the mitotic checkpoint complex (MCC). Nek2A binds preferentially the open conformation of the APC/C MCC complex where the APC/C catalytic site is liberated from the MCC inhibition. Nek2A, which exists as a dimer, binds through its C‐terminal MR tail dipeptide in two distinct sites on the APC/C which overlap with MCC binding sites. Contrary to the other prometaphase‐specific substrate cyclin A, which can preferentially be ubiquitinated via the UbcH10‐APC/C complex, Nek2A can be efficiently ubiquitinated by APC/C complexes with both UbcH10 and UbcH5. Abstract : The APC/C regulates mitosis by catalysing the sequential ubiquitination of specific substrates. This study shows how the APC/C ubiquitinates the Nek2A kinase in prometaphase when the APC/C is inhibited by the mitotic checkpoint complex (MCC).